2003
DOI: 10.1002/pssc.200303456
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of InN growth on Ga‐ and N‐polarity GaN templates by molecular‐beam epitaxy

Abstract: Molecular-beam epitaxial growth of InN was investigated on Ga-and N-polar GaN templates. It was found that InN layers could be grown at higher temperature on N-polar GaN than on Ga-polar one, on which InN films succeeded the cation-or anion-polarity, respectively. The growth temperature of In-polar InN was limited below 500 °C; while that of N-polar InN could be as high as 600 °C. In the upper-limit growth temperature range for N-polar InN, atomic-height growth steps could be observed on the surface. The possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…On the other hand, for the (10-12) peak, the FWHM in the case of no buffer layer is larger than that in the case of using a buffer layer. It was also found that the FWHM for the (10-12) peak of h-InN grown with a buffer layer were not too large considering that the FWHM for the (0002) peak are around 900 arcsec [4,5]. When the buffer layer is used and the h-InN layer grown is composed of single domain, the twist of the crystal is considerably restricted due to the small lattice mismatch between h-InN(10-10) and 3C-SiC(110).…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, for the (10-12) peak, the FWHM in the case of no buffer layer is larger than that in the case of using a buffer layer. It was also found that the FWHM for the (10-12) peak of h-InN grown with a buffer layer were not too large considering that the FWHM for the (0002) peak are around 900 arcsec [4,5]. When the buffer layer is used and the h-InN layer grown is composed of single domain, the twist of the crystal is considerably restricted due to the small lattice mismatch between h-InN(10-10) and 3C-SiC(110).…”
Section: Resultsmentioning
confidence: 96%
“…In order to successfully grow InN film, many groups used relatively low growth temperatures (~460-550 °C) [6][7][8][9]. We have reported that the maximum growth temperature was different for successful epitaxy of InN films at different polarities, where the N-polar InN films could be grown at about 100 °C higher than In-polar ones [10]. As we know, high temperature is better for getting high crystalline quality and fabricating devices structures based on III-nitrides alloys including InN.…”
Section: Introductionmentioning
confidence: 96%
“…N-polarity GaN was used as the buffer layer. We have already reported that the epitaxy temperature of InN can be about 100 o C higher in N-polarity than In-polarity [9,10]. We expected the N-polarity growth regime would be better even for the growths of In-rich AlInN ternary alloys and InN/AlInN MQWs.…”
mentioning
confidence: 93%